Digital resistance: #SaveSheikhJarrah and the role of Palestinian activism on social media - Kelsch, Sophia Maria (2022)
This Master dissertation explores the evolution of transnational social movements and the rise of digital mobilisation in the twenty-first century, with a focus on the Palestinian case. Parallel to the theoretical study of social movements, the core of this work represents a synopsis of Palestinian resistance history, with a focus on the period between 1936 and today's popular struggles, particularly digital resistance in the age of social media. More in detail, this dissertation is based on a case study around the hashtag #SaveSheikJarrah, which went viral in May 2021. The hashtag represents a generational outcry against the Israeli occupation and settler-colonial evictions in the East Jerusalem neighbourhood of Sheikh Jarrah and has brought unprecedented attention for the Palestinian cause on a global level. This dissertation contributes to the documentation of activists' narratives and maps the meanings of Palestinian resistance in the new era of social media within a broader historical context. Furthermore, the rather novel and multidisciplinary research approach, which combines digital ethnography with interviews with activists, makes an original contribution to Palestine studies within Portuguese academia, which constitutes a major research gap that exists to this day.